2020
DOI: 10.1002/cncr.32948
|View full text |Cite
|
Sign up to set email alerts
|

Association of GSTM1 null variant with anthracycline‐related cardiomyopathy after childhood cancer—A Children's Oncology Group ALTE03N1 report

Abstract: BackgroundAnthracycline‐related cardiomyopathy is a leading cause of late morbidity in childhood cancer survivors. Glutathione S‐transferases (GSTs) are a class of phase II detoxification enzymes that facilitate the elimination of anthracyclines. As free‐radical scavengers, GSTs could play a role in oxidative damage‐induced cardiomyopathy. Associations between the GSTμ1 (GSTM1) null genotype and iron‐overload–related cardiomyopathy have been reported in patients with thalassemia.MethodsThe authors sought to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…The existing evidence has been used to construct the proposed pathophysiologic mechanism of anthracycline-related cardiomyopathy in the Central Illustration . Whereas some studies utilized childhood cancer ( 21 25 , 27 , 28 , 45 47 ) or adult-onset cancer populations ( 26 , 48 55 ), others included patients across the age spectrum ( 20 , 30 , 56 , 57 ). Several studies examined homogeneous cancer populations (leukemia, osteosarcoma, breast cancer, lymphoma), whereas others examined a mix of several cancers.…”
Section: Pathogenesis Of Anthracycline-related Cardiomyopathymentioning
confidence: 99%
See 2 more Smart Citations
“…The existing evidence has been used to construct the proposed pathophysiologic mechanism of anthracycline-related cardiomyopathy in the Central Illustration . Whereas some studies utilized childhood cancer ( 21 25 , 27 , 28 , 45 47 ) or adult-onset cancer populations ( 26 , 48 55 ), others included patients across the age spectrum ( 20 , 30 , 56 , 57 ). Several studies examined homogeneous cancer populations (leukemia, osteosarcoma, breast cancer, lymphoma), whereas others examined a mix of several cancers.…”
Section: Pathogenesis Of Anthracycline-related Cardiomyopathymentioning
confidence: 99%
“…Twelve of the 26 studies (46%) reviewed here, did not attempt a replication of their salient findings. However, some of these studies were either examining a single SNP with targeted activity and established mechanism of cardiotoxicity ( 28 , 57 ) or had extended their findings by demonstrating differential gene expression ( 47 ) or by validating in preclinical mouse models ( 26 ). Furthermore, some of these studies replicated findings from previous studies ( 30 , 48 51 ).…”
Section: Pathogenesis Of Anthracycline-related Cardiomyopathymentioning
confidence: 99%
See 1 more Smart Citation
“…MLH1 and MLH2 are genes playing a role in DNA repair and GSTs are detoxifying enzymes. Another recent study by Singh et al (2020) investigated the role of GSTM1 in chronic anthracycline-induced cardiotoxicity. They found that patients carrying GSTM1 null genotype (i.e.…”
Section: Other Polymorphismsmentioning
confidence: 99%
“…A recent study carried out on 167 anthracycline-exposed childhood cancer survivors (75 cases and 92 matched controls with different diagnosis including 40 with bone tumors) reported that patients who had the GSTM1 null genotype had a significantly higher risk to develop cardiomyopathy [ 121 ]. GSTM1 expression downregulation in patients with the null phenotype in peripheral blood was confirmed by array and RNA-Seq analyses.…”
Section: Gene Polymorphisms Associated With Toxicitiesmentioning
confidence: 99%